2014
DOI: 10.1080/02626667.2014.910305
|View full text |Cite
|
Sign up to set email alerts
|

Effects of urbanization variables on model parameters for watershed divisions

Abstract: A semi-distributed model with a parallel connection was applied to examine the effects of urbanization variables. Data were obtained from watershed divisions that were characterized by various degrees of urbanization. The mean rainfall was calculated using the kriging method. The model inputs were obtained by subtracting mean rainfall from Ф-index values, based on the spatially uniform loss assumption. Regression analysis was applied to determine the relationship between the parameters of 64 calibrations and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…The overland parameter responded more sensitively to the imperviousness than the channel parameter did. Chen et al (2014) confirmed that the overland storage changes more sensitively in response to the impervious changes than the channel storage does. Therefore, the channel storages were regarded as constants in this study.…”
Section: Storage Changes Resulting From Imperviousness Changes In Thesupporting
confidence: 81%
See 1 more Smart Citation
“…The overland parameter responded more sensitively to the imperviousness than the channel parameter did. Chen et al (2014) confirmed that the overland storage changes more sensitively in response to the impervious changes than the channel storage does. Therefore, the channel storages were regarded as constants in this study.…”
Section: Storage Changes Resulting From Imperviousness Changes In Thesupporting
confidence: 81%
“…Hydrologists are concerned that changing imperviousness might alter the infiltration mechanism in the hydrological cycle and change watershed response (Legesse et al 2003;Hagg et al 2007;Ackerman and Stein 2008;Cheng et al 2010;Cheng 2011;Chen et al 2014;Zhang and Shuster 2014). Various runoff hydrographs are represented by different characteristics related to spatial rainfall and outlet-streamflow observations over time (Cheng et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Toward this aim, attempts at expressing model parameters in terms of urbanization measures exist in the literature. For example, Cheng et al [51] and Chen et al [52] aimed to relate Nash model parameters to basic urban indicators, such as imperviousness and population. Kjeldsen et al [53] related the four parameters of a basically nonurban event-based and conceptual model to the urbanized proportion of seven catchments in the United Kingdom.…”
Section: Application Of Rf For Model Regionalization In Multiple Landmentioning
confidence: 99%
“…Watershed delimitation is very important in the subject of water or sedimentary transport in disaster and environmental fields [3,4], and basin morphometric parameters largely control a catchment's hydrology response [5]. In flood control management studies, different watershed division schemes can produce different simulation quantity results in the distribution of rainwater and sediment at the catchment scale [6][7][8].…”
Section: Introductionmentioning
confidence: 99%